2017
DOI: 10.28948/ngumuh.297720
|View full text |Cite
|
Sign up to set email alerts
|

Ami̇gdali̇n Ve Özelli̇kleri̇

Abstract: ÖZDoğada en çok karşılaşılan siyanojenik glikozit olan amigdalin kayısı, badem, kiraz, elma, erik, armut ve şeftali gibi meyvelerin çekirdeklerinde bulunur. Amigdalin, D(-)-mandelonitril-β-D-gentiobiyozit, D(-)-amigdalin, R-amigdalin, laetril ve vitamin B 17 gibi isimlerle de anılmaktadır. Amigdalinin parçalanması enzimatik aktivite, ısıl işlem, mineral asitler ve yüksek askorbik asit konsantrasyonları ile gerçekleşebilir ve parçalanma sonucunda zehirli hidrojen siyanür oluşur. Amigdalin, alyuvar üretiminin ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…AMG (C20H27NO11) is the most commonly encountered cyanogenic diglycoside found in plants belonging to the especially genus Prunus of the Rosaceae family especially in fruit kernels. 4 Fruit kernels are considered to be unwanted parts of the fruit; but these kernels can represent valuable products with a large industrial potential. 5 Cyanogenic glycosides are a large group of secondary metabolites including various plants that are commonly consumed by humans.…”
Section: Introduction *mentioning
confidence: 99%
See 1 more Smart Citation
“…AMG (C20H27NO11) is the most commonly encountered cyanogenic diglycoside found in plants belonging to the especially genus Prunus of the Rosaceae family especially in fruit kernels. 4 Fruit kernels are considered to be unwanted parts of the fruit; but these kernels can represent valuable products with a large industrial potential. 5 Cyanogenic glycosides are a large group of secondary metabolites including various plants that are commonly consumed by humans.…”
Section: Introduction *mentioning
confidence: 99%
“…In addition, there are many studies in which AMG was determined by using various extraction methods and solvents in the extraction of AMG from different fruit seeds. 4,6,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] For example; apricot, cherry, apple, 6 pear, nectarines, plum and bitter almond 4 and quince 14 belong to the Rosaceae family; watermelon belongs to the Cucurbitaceae family; 15 lemon belongs to the Rutaceae family; 16 pomegranate belongs to the Lythraceae family; 17 rambutan 18 and longan 19 belong to the Sapindaceae family; papaya belongs to the Cacicaceae family 20 and guava belongs to the Myrtaceae family. 21 Miao et al 22 reported that amount of AMG for apricot kernel as 0.18 mg/mL, Koo et al 23 reported that for apricot as 1.73 mg/g, Lee et al 24 reported that for apricot as 40060.34 mg/kg, Femenia et al 25 reported that for apricot as 5.5 g/100g, Yildirim et al 26 reported that for apricot as 22.53 mg/g, Lv et al 27 reported that for apricot and hairy cherry kernels, respectively as; in ultrasonic extraction, 1.71% and 1.67%; in Soxhlet extraction, 2.03% and 2.11%; in reflux extraction, 4.31% and 4.09%, Bolarinwa et al 10 reported that for apricot as 14.37 mg/g, for cherry as 3.89 mg/g, for nectarine as 0.12 mg/g, for peach as 6.81 mg/g, for plum as 17.49 mg/g, for apple as 2.96 mg/g and for pear as 1.29 mg/g, Zhao 28 reported that for apricot as 0.11%-3.26%, for peach as 0.13%-3.73%, for plum as 0.28%-4.91%, and for bitter apricot as 0.39%-5.1%...…”
Section: Introduction *mentioning
confidence: 99%